Inflation in Albania - Rother, Philipp (IMF Working Papers; Working Paper ;, 2000)
As Albania has succeeded in reducing inflation to very low levels, understanding the driving forces behind the behavior of the price level becomes increasingly important for policy design. In particular, persistent changes in relative prices may contribute to movements of the aggregate price level, and policymakers need to decide to what extent such effects should be accommodated. The present study provides insight into the nature and extent of relative price adjustments during the transition period, and argues that some of their inflationary effects should not be resisted.